2020
DOI: 10.1002/art.41385
|View full text |Cite
|
Sign up to set email alerts
|

Different Hierarchies of Anti–Modified Protein Autoantibody Reactivities in Rheumatoid Arthritis

Abstract: Objective. Anti-citrullinated protein antibodies (ACPAs) are a hallmark of seropositive rheumatoid arthritis (RA). Yet, the precise disease-relevant autoantigens that are targeted by ACPAs remains a matter of debate. This study utilized patient-derived monoclonal ACPAs, rather than serum autoantibody analysis, to characterize the multireactivity to different protein modifications and to reveal autoantibody subsets in patients with RA. Methods. Twelve human monoclonal ACPAs (positive by the second-generation cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 52 publications
5
90
0
Order By: Relevance
“…Since it has been recently shown that ACPA can cross-react against multiple peptides (especially those that contain a common citrulline-glycine motif; ref. 34), we examined the specificity and potential cross-reactivity between cit-TNC17-and cit-TNC56-reactive antibodies by performing inhibition experiments using sera from subjects that were double-reactive for cit-TNC17 and cit-TNC56 antibodies. Absorption by the homologous peptide was efficient for both cit-TNC17 and cit-TNC56 ( Figure 5, left panels), while cross-reactivity was limited; only partial inhibition was observed in serum 2 (maximum inhibition: 24.8% for cit-TNC56 versus cit-TNC17) and serum 6 (maximum inhibition: 22% for cit-TNC17 versus cit-TNC56 and 43% for citTNC56 versus cit-TNC17) ( Figure 5, middle panels).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it has been recently shown that ACPA can cross-react against multiple peptides (especially those that contain a common citrulline-glycine motif; ref. 34), we examined the specificity and potential cross-reactivity between cit-TNC17-and cit-TNC56-reactive antibodies by performing inhibition experiments using sera from subjects that were double-reactive for cit-TNC17 and cit-TNC56 antibodies. Absorption by the homologous peptide was efficient for both cit-TNC17 and cit-TNC56 ( Figure 5, left panels), while cross-reactivity was limited; only partial inhibition was observed in serum 2 (maximum inhibition: 24.8% for cit-TNC56 versus cit-TNC17) and serum 6 (maximum inhibition: 22% for cit-TNC17 versus cit-TNC56 and 43% for citTNC56 versus cit-TNC17) ( Figure 5, middle panels).…”
Section: Resultsmentioning
confidence: 99%
“…ACPA and rheumatoid factor are diagnostic in RA, can precede disease by up to 10 years, and are thought to participate in joint pathology (2)(3)(4). ACPA have been shown to target multiple citrullinated antigens, with some exhibiting narrow or single-antigen specificity and others demonstrating substantial cross-reactivity toward shared consensus motifs (34). Notably, the number of ACPA specificities expands as individuals progress from pre-RA to develop inflammatory arthritis (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 However, even a highly specific ACPA monoclonal antibody can cross-react toward various post translational modifications (citrulline, homocitrulline and acetylide). 23 , 24 Likewise, immunization with a specific antigen can generate different AMPA. 25 An individual patient may have various AMPA clones with distinct reactivity profiles capable of recognizing multiple amino acid motifs, rather than specific proteins.…”
Section: Discussionmentioning
confidence: 99%
“… 25 An individual patient may have various AMPA clones with distinct reactivity profiles capable of recognizing multiple amino acid motifs, rather than specific proteins. 23 25 It might be speculated that PR AMPA clones have a narrowed amino acid motif recognition profile, ensuing a lower cross reactivity.…”
Section: Discussionmentioning
confidence: 99%